PELAKSANAAN PEMBAGIAN HARTA WARISAN TERHADAP AHLI WARIS PENGGANTI MENURUT HUKUM ISLAM DAN HUKUM PERDATA: Hilman Ajie Indra - admin, admin; Hariz Hamdallah, Muhammad Andika (Fakultas Hukum Universitas Islam Jakarta, 2018)
The result of his research is that the position of heir substitute according to Islamic law has been explained in Article 185 paragraph (2) Compilation of Islamic Law which states